Developing iron-based anionic redox couples for thermogalvanic cells: towards the replacement of the ferricyanide/ferrocyanide redox couple. Issue 22 (1st November 2021) - Buckingham, Mark A.; Laws, Kristine; Cross, Edward; Surman, Andrew J.; Aldous, Leigh
Abstract : Thermogalvanic devices require anionic and cationic species; the rational development of safe(r) iron-based anionic redox couples was explored. Abstract : Thermogalvanic devices can harvest wasted thermal energy; a waste product that is generated by humanity in staggering abundance. However, the incorporation of thermogalvanic devices in applications from hot, industrial environments through to waste body heat harvesting necessitates safe chemicals. In particular, since the redox active ions are the charge carriers the chemistry of these is crucial; the bigger and more powerful the device, the greater the abundance of these chemicals. The anionic ferricyanide/ferrocyanide ([Fe(CN)6 ] 3−/4− ) redox couple is arguably the most widely utilised and investigated thermogalvanic electrolyte, but has inherent (in)stability issues, and therefore safety issues. This study has investigated a wide range of anionic polycarboxylate and polyaminocarboxylate ligands in conjunction with iron(ii /iii ) chloride (FeCl2/3 ) in an effort to develop a safer [Fe(CN)6 ] 3−/4− -replacement. Detailed electrochemical and spectroscopic characterisation was used across the wide range of ligands investigated, and several were found to be viable for use in thermogalvanic cells. In particular, optimised nitriloacetic acid was found to yield a redox-active complex, [Fe(NTA)2 ] 3−/4−, with a good Seebeck coefficient (−1.35 mV K −1 ) on par with [Fe(CN)6 ] 3−/4− . However, diethylenetriaminepentaacetic acid (to form [Fe(DEPTA)] 2−/3− ) demonstrated the optimum compromise between thermodynamic and kinetic properties; this was used to prepare an in-series thermogalvanic device with the parent Fe 2+/3+ species. Benchmarking against relative costs, and the principles of green chemistry and green chemical engineering was used to identify the relative merits of the different systems.